DNA sequence analysis of spontaneous mutations at the aprt locus of hamster cells. - Nalbantoglu, J (1987)
To determine the nature of spontaneous mutational events in cellular genes in hamster cells, mutant adenine phosphoribosyltransferase (aprt) genes were cloned and the regions to which we mapped alterations were sequenced. A variety of nucleotide changes were found to occur in the 12 mutant genes analyzed. Most mutations were simple base-pair substitutions-transitions (both G X C----A X T and A X T----G X C) and transversions. The only multiple mutation was a simple transition next to a single-base-pair insertion. Of the 12 mutations, 4 were more complex, involving small deletions or duplications. Two of these were similar to previously described deletions in that they occurred between short direct sequence repeats. No hot spots were detected. Three independent mutations were characterized at one restriction endonuclease site, although no other mutations were detected in the nucleotides surrounding this site in other mutant strains. At a functional level, sequence changes were either in exons (resulting in missense and, in one instance, nonsense mutations) or at splicing sites.